2021
DOI: 10.1002/cpp.2699
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to determine how service provider practises impact effective service provision to lesbian, gay and bisexual consumers in a mental health setting

Abstract: Lesbian, gay and bisexual (LGB) consumers utilize mental health services at a similar rate to their heterosexual counterparts yet report greater dissatisfaction with service quality. This dissatisfaction may be explained by service provider's microaggressions, stemming from a lack of cultural competence in working with LGB consumers. This systematic review examines how the practises of mental health service providers impacted effective service provision to LGB people in a clinical practice. Five health databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
14
0
1
Order By: Relevance
“…Likewise, our results indicate that therapists must acknowledge the wide-ranging impact of social and systemic injustice relating to bisexual women's multiple marginalized identities when creating a clinical formulation of their mental health difficulties. Previous research has, however, found that practitioners from a range of healthcare professions, including clinical and counseling psychology, report feeling unsure of ways to communicate with LGBTQ+ clients (Bishop et al, 2022). To do this, it is strongly recommended that therapists ask about clients' marginalized identities within assessments (Dunlop, Woods, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our results indicate that therapists must acknowledge the wide-ranging impact of social and systemic injustice relating to bisexual women's multiple marginalized identities when creating a clinical formulation of their mental health difficulties. Previous research has, however, found that practitioners from a range of healthcare professions, including clinical and counseling psychology, report feeling unsure of ways to communicate with LGBTQ+ clients (Bishop et al, 2022). To do this, it is strongly recommended that therapists ask about clients' marginalized identities within assessments (Dunlop, Woods, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…King et al, 2007;McNamara & Wilson, 2020;O'Shaughnessy & Speir, 2018;Singh & Shelton, 2011). These reviews have added to our understanding of what facilitates psychotherapy with SGM clients including (a) the importance of therapists' attitudes and knowledge about SGM clients in delivering beneficial psychotherapy (Bieschke et al, 2007;Bishop et al, 2022;Compton & Morgan, 2022; M. B. King et al, 2007;McNamara & Wilson, 2020;O'Shaughnessy & Speir, 2018); (b) that there is minimal evidence to support the hypothesis that matching clients and therapists on sexual or gender identities improves outcomes (Compton & Morgan, 2022; A. E. Ellis et al, 2020; M. B.…”
Section: Existing Systematic Reviewsmentioning
confidence: 99%
“…The tripartite model of cultural competence describes three core components of cultural competence: awareness of one's own beliefs, biases and attitudes; knowledge and understanding of the cultural group including expectations for the therapeutic relationship and how one's own cultural background comes into play; and skills and tools to provide culturally sensitive assessment and intervention (Crisp, 2006; Sue et al, 1982). A systematic review examining how culturally affirming practices impact service provision to LGB people has highlighted that poor cultural competence often results from negative attitudes towards LGB people, lack of knowledge about the impact of minority stress on LGB and poor practitioner skill in demonstrating affirming care (Bishop et al, 2021b). Understanding the impact of cultural competence on therapeutic outcomes is important because it allows therapists to provide best practice care to LGB clients.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has explored the challenges that exist for therapists to attain the cultural competence to inform their inclusive practice (Bishop et al, 2021b). Previous research on a cohort of graduate counsellors demonstrated that passive lectures on culturally affirming practice were insufficient to promote the use of cultural competence practices in a clinical setting (Graham et al, 2012).…”
Section: Introductionmentioning
confidence: 99%